Tuberculosis in Humans and Cattle in Jigawa State, Nigeria: Risk Factors Analysis - S. Ibrahim; S. I. B. Cadmus; J. U. Umoh; I. Ajogi; U. M. Farouk; U. B. Abubakar; A. C. Kudi (Veterinary Medicine International)
A cross-sectional study was conducted from September 2008 to March 2009 to identify risk factors for BTB in cattle and humans in Jigawa State, Nigeria. A total of 855 cattle belonging to 17 households were subjected to comparative intradermal tuberculin test (CITT) while interviewer-administered questionnaire was used to obtains information on the risk factors. Twenty-two (22) respondent (5%) amongst the families sampled had TB or clinical signs suggestive of TB, while 9 (2%) had reactor cattle in their herds; However, no statistically significant association (𝑃≥0.05) was observed between reactor cattle and human TB cases in the households. The habit of milk and meat consumption was found to be affected by occupation and location of the household residence. None of these risk factors (food consumption, living with livestock in the same house, and presence of BTB-positive cattle) were found to be statistically significant.